PENERAPAN MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA - Sri Yunita Ningsih; Suci Andriani (MES: Journal of Mathematics Education and Science, 2017)
Abstract. The purpose of this study was to determine differences in the ability of understanding mathematical concepts eighth grade junior high school 3 Lala River. This is the kind of research is a Quasi Experiment, design Nonequivalen control group design. Data analysis techniques in this test using normality test, homogeneity and hypothesis testing. Based on the calculation hypothesis test showed significant values t_test = 1.619 t_table = 2.012. So it can be concluded that the ability of students' understanding of mathematical concepts with the application of Inside Outside Circle learning model is better than the ability of understanding mathematical concepts students by using conventional learning models in class VIII School SMP Negeri 3 Sungai Lala.Keywords: Inside Outside Circle, Understanding of Mathematical ConceptAbstrak. Tujuan penelitian ini adalah untuk mengetahui perbedaan kemampuan pemahaman konsep matematika siswa kelas VIII Sekolah Menengah Pertama Negeri 3 Sungai Lala. Jenis penelitian ini adalah adalah Quasi Experiment, dengan desain Nonequivalen control grup desain. Teknik analisis data dalam pengujian ini menggunakan uji normalitas, homogenitas dan uji hipotesis.  Berdasarkan hasil perhitungan uji hipotesis menunjukkan nilai signifikan  = 1,619  = 2,012. jadi dapat disimpulkan bahwa kemampuan pemahaman konsep matematika siswa dengan penerapan model pembelajaran Inside Outside Circlelebih baik daripada kemampuan pemahaman konsep matematika siswa dengan menggunakan model pembelajaran konvensional di kelas VIII Sekolah Menengah Pertama Negeri 3 Sungai Lala.Kata Kunci: Pemahaman Konsep dan Inside Outside Circle